Potential of NTFPs in Income and Employment Generation for Tribals of Polo Forest, Sabarkantha, Gujarat - Mewada, Ketan Babubhai; Ant, H. M. (Indian Forester, 2020)
The present survey is the most elaborate comprised study on Non-Timber Forest Products (NTFPs) collection along with its economic contribution to the tribal economy of Polo forests. In the study, a total of 31 villages of Polo forests have been sampled to calculate a total collection of NTFPs. During the study, 10% households of the total households from each village were interviewed with the help of a predesigned questionnaire. The primary level survey revealed that NTFPs played a remarkable role in the tribals economy of Polo forests from the contribution of a total of 57 NTFPs which are being collected from 8 different parts of 48 plant species products and 2 animal products. These NTFPs have generated an income oft 12.74 million/annum of which maximum part comes from nonrecorded trades. The current estimation of income generation revealed that maximum economic contribution was found to be in Mahuwa (29%) followed by Timru (25%), Puvad (7%) and Salai Guggal (6%). The study also revealed that in Polo forests, Kathodi community is the most forestdependent community that collects almost all types of NTFPs available during the year. The current study concluded the role of NTFPs in the tribal economy and various factors affecting the collection and trade.